Analysis of Dengue Fever Cases Based on Climate Factors in Semarang City 2020-2022 - Suciningsih, Ragil; Khimayah (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to visually analyze the impact of rainfall, temperature, and humidity on the incidence of dengue fever cases in Semarang City in 2020-2022. Research on the impact of climate on dengue fever is important in order to help develop more effective mitigation strategies in preventing dengue outbreaks in the future. Methods: This study used secondary data from Semarang City Health Office and BMKG in the form of dengue fever incidence data and climate data (temperature, rainfall, and humidity), with an ecological study design according to time series. The analysis used was descriptive analysis with visualization in the form of graphs to illustrate case trends and their relationship with temperature, humidity, and rainfall factors. Results: The analysis showed that from 2020 to 2022, the incidence rate of DHF cases in Semarang City was low and relatively stable at below 10 per 100,000 population. Although there were some fluctuations, there were no significant spikes in the number of cases during these three years. In general, the temperature from 2020 to 2022 was relatively stable, with no significant changes in temperature in each month, while humidity and rainfall showed similar trends, with fluctuating trends. The visualization results also show that the number of Dengue incidents tends to be more influenced by the air temperature factor. Conclusion: The observed air temperature factor tends to be more influential on the dengue fever incidence rate in Semarang City from 2020 to 2022 compared to the temperature and humidity factors.